WIDEBAND DIGITAL RECEIVER/PULSE ANALYZER - Vynogradov, V. V.; Volkov, V. A.; Kozhyn, R. V.; Sosnytskiy, S. V.; Vavriv, D. M.; Vasilyev, O. Y.; Bulakh, E. V.; Usik, P. V.; Kuzin, A. I. (Видавничий дім «Академперіодика», 2015)
The experience of development of a digital receiver/pulse analyzer is described. The measuring set has a modular structure and consists of three functionally independent systems: Radio Frequency Tuner, Digital Pulse Analyzer, and Data Record and Storage System. The ultra-wideband Tuner operates within 0.4 to 18 GHz. The high performance Pulse Analyzer detects up to 2 million pulses per second in real time. The Data Recording System is capable of recording raw data and results of processing for as long as 40 min at the rate of up to 3 GB/s. This measuring set is perfectly suitable for usage in radiolocation, radioastronomy, spectroscopy, in the systems for radioemission monitoring and in within the measuring-calibrating equipment.Key words: wideband digital receiver, digital signal processing, time-and-frequency analysisManuscript submitted 17.04.2015Radio phys. radio astron. 2015, 20(2): 168-179REFERENCES1. 2006. Russia's Arms and Technologies XXI Encyclopedia: Volume XIII, Control, Communication and Radio Electronic Warfare Systems. Moscow. Russia: Publ. House Arms and Technologies. 2. TSUI, J. B.,  1986. Microwave Receivers with Electronic Warfare Applications. New York: Wiley-Interscience. 3. RYABOV, V. B., VAVRIV, D. M., ZARKA, P., RYABOV, B. P., KOZHIN, R. V., VINOGRADOV, V. V. and DENIS, L., 2010. Alow-noise, high-dynamic-range, digital receiver for radio astronomy applications: an efficient solution for observing radio-bursts from Jupiter, the Sun, pulsars, and other astrophysical plasmas below 30 MHz. Astron. Astrophys. vol. 510, id. A16. DOI: https://doi.org/10.1051/0004-6361/200913335 4. KOZHIN, R. V., VINOGRADOV, V. V. and VAVRIV, D. M.,  2007. Lownoise, high dynamic range digital receiver/spectrometer for radio astronomy applications. In: Proceedings of the 6-th Int. Symp. MSMW'07. Kharkiv, Ukraine, June 25-30, 2007, pp.736–738. 5. NAMGOONG, W., 2003. Channelized Digital Ultrawideband Receive. IEEE Trans. Wireless Commun. vol. 2, no. 3, pp. 502–510. DOI: https://doi.org/10.1109/TWC.2003.811177 6.  VASILYEV, O. Y., KUZIN, A. I., KRAVTSOV, A. A., BULAKH, E. V., VINOGRADOV V. V. and VAVRIV, D. M.,  2014. Multifunctional Digital Receiver-Spectrometer. Radio Phys. Radio Astron. – vol. 19, no. 3, pp. 276–289 (in Russian). 7. ZAHIRNIAK, D. R., SHARPIN, D. L. and FIELDS, T. W., 1998. A Hardware-Efficient, Multirate, Digital Channelized Receiver Architecture. IEEE Trans. Aerosp. Electron. Syst. vol. 34, no. 1, pp. 137–152. DOI: https://doi.org/10.1109/7.640270 8. LOPEZ-RISUENO, G., GRAJAL, J. and SANZ-OSORIO, A., 2005. DigitalChannelized Receiver Based on Time-Frequency Analysis for Signal Interception. IEEE Tran. Aerosp. Electron. Syst. vol. 41, no. 3, pp. 879–898. DOI: https://doi.org/10.1109/TAES.2005.1541437 9.  VOLKOV, V. A., VAVRIV, D. M., BULAKH, E. V. and KRAVTSOV, A. A. , 2014. High sensitivity 0.5 to 19.5 GHz receiver with 1.1-GHz instantaneous bandwidth. Radio Phys. Radio Astron.  vol. 19, no. 4, pp. 375–380. 10. V VOLKOV, V. A., VAVRIV, D. M., BULAKH E., V. and KRAVTSOV, A. A., 2014. Broadband Low-Noise Receiver Front-End with Ultrawide Bandwidth. In: Proceedings of the 20th International Conference on Microwaves, Radar and Wireless Communications (MIKON 2014). Gdansk, Poland, 16-18 June, 2014, vol. 2, pp. 675–678. DOI: https://doi.org/10.1109/MIKON.2014.6899983 11. KENYON, T.,  2002. High Performance Data Network Design: Design Techniques and Tools.USA: Digital Press. 12. PLAVEC, F., FORT, B., VRANESIC, Z. G. and BROWN, S. D., 2005. Experiences with Soft-Core Processor Design. In: Proceedings of the 19th IEEE International Parallel and Distributed Processing Symposium (IPDPS'05). Denver, Co, USA, April 3-8, 2005, pp. 167b. DOI: https://doi.org/10.1109/ipdps.2005.209 13. DURAN, B. S. and ODELL P. L., 1974. Claster Analysis. A Survey. Berlin – Heildelberg -New York: Springer-Verlag 14. CARPENTIERI, E. and CUOMO, S., 2008. An adaptive threshold algorithm for detection of pulse radar signals. Radar Conference, RADAR '08, IEEE. Rome, Italy, 26-30 May 2008. DOI: https://doi.org/10.1109/RADAR.2008.4720754 15. ALY, O. A. M., OMAR, A. S., and ELSHERBENY, A. Z., 2006. Detection and localization of RF radar pulses in noise environments using wavelet packet transform and higher order statistics. Prog. Electromagn. Res. vol. 58. pp. 301–317. DOI: https://doi.org/10.2528/PIER05070204